Partially Depleted Silicon-on-Ferroelectric Insulator Field Effect Transistor- Parametrization & Design Optimization for Minimum Subthreshold Swing. Issue 10 (October 2015) - Es-Sakhi, A.D.; Chowdhury, M.H.
Abstract This paper presents the concept of a new field effect transistor based on ferroelectric insulator. The proposed design is named Partially Depleted Silicon-on-Ferroelectric Insulator Field Effect Transistor (PD-SOFFET). The design combines the concepts of negative capacitance in ferroelectric material and silicon-on-insulator (SOI) device. The structure varies from the conventional SOI technology by substituting the buried SiO2 with a layer of ferroelectric insulator. This new material stack can extract an effective negative capacitance (NC) in the body of the device. The NC effect can provide internal signal boosting. It is demonstrated that the subthreshold swing and the threshold voltage of the proposed device can be lowered by carefully selecting the doping density, the types of the gate oxide and the thicknesses of the ferroelectric film, the silicon layer above the buried insulator and the gate oxide. Lower subthreshold swing is a prime requirement for ultra-low-power design. This paper focuses on studying several parameters to tune the subthreshold swing of the SOFFET device. We have recently introduced the concept of the new transistor, SOFFET, with ferroelectric insulator embedded inside the silicon substrate to lower the subthreshold swing. This paper investigates the impacts of different oxide materials, ferroelectric thicknesses and doping profiles on the negative capacitance inside the body of the proposed PD-SOFFET. It is observed that some emerging gate oxide materials can improve subthreshold flexibility, lower leakage and provide better control over the channel in the proposed device.